IFTU and LSI Conference re Spain (circular) - Labour and Socialist International; Stolz, George
022_0014-001 FÉDÉRATION SYNDICALE INTERNATIONALE INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONALER GEWERKSCHAFTSBUND 9, AVENUE D'ORSAY, PARIS - VIIe ADRESSE TÉLÉGRAPHIQUE: TELEGRAPHIC ADDRESS: INTERFED, PARIS TELEGRAMMADRESSE: TÉLÉPHONE: INVALIDES 45-88 Situation Espagne 92 St/G/sz FOR YOUR INFORMATION 2nd March, 1937 To Affiliated National Centres To International Trade Secretariats To Delegates Dear Comrades, IFTU AND LSI CONFERENCE RE SPAIN We are sending you herewith a delegate's card to the International Conference on Spain to be held on the 10th and 11th March, 1937, in the Library of the Central Hall, Westminster, London. Please have that card signed by the delegate, mentioning the organisation concerned, and show it to the Immigration Officer at the passport control. If these cards are produced at the ports duly signed and filled in, there will be no difficulty, otherwise the persons may be held up. The British Home Office, in the desire of refraining from intervention in the Spanish trouble, will not allow anything that may be taken as intervention and refuse facilities for foreign visitors whose purpose is to further the interests or engage in propaganda on behalf of either side. The British Government, however, is ready to do everything to facilitate our meetings and will admit delegates who will not take part in any meeting or demonstration other than those of the Conference and the Demonstration arranged in aid of the International Solidarity Fund by the National Council of Labour. (There is evidence of the need of caution as it is learned that a Conference is being called by another organisation for the Saturday following our Conference, to which Spanish and other continental delegates are invited to participate. The Home Office will not allow these invitations to be accepted.) Yours fraternally, G. Stolz Assistant Secretary 292/946/22/13